Effects of climate upon civilization - Arbuthnot, William Sherman (My University, 1891)
Introduction: Although, the tropical regions were inhabited at a very early date, it is evident that the advance of civilization in this climate has scarcely been perceptible. In early times much more than of late the abode of man had to be in close proximity with that of vegetable life, and as the tropical contained the largest growth of plant life, it was essential that the aboriginal man should be found in these parts; but as one go from a warm to a colder region, either from the equator toward the temperate region or ascend a high mountain, one find a marked variation in vegetable growth, the same is true of man, although the change is not so distinctly marked as it is with plants, but in noticing the whole extent of latitude great variation can be seen in both the mental, moral, and physical condition of the inhabitants.
Citation: Arbuthnot, William Sherman. Effects of climate upon civilization. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Climate; tropical; civilization; Theses; Manuscripts (documents)